Polimorfismo genético GSTM1 e GSTT1 em pacientes com excesso de peso e diabéticos infectados por COVID-19 - Reginatto, Danglei Cristina (2023)
The number of people infected and killed by the SARS-Cov-2 virus shows the impact of the pandemic. The group of people prone to severe illness and death include the elderly, diabetics, cardiovascular, respiratory and kidney diseases. However, obesity has revealed a serious condition and negative prognosis, being in Brazil the main cause of morbidity associated with death in individuals under 60 years of age. Current studies relate the GSTT1 and GSTM1 genes as a risk factor for the development of some diseases, including the severity of covid-19. To identify the presence of the GSTT1 and GSTM1 genetic polymorphism in overweight and diabetic patients infected with Covid-19. This is a cross-sectional study, carried out between the years 2020 and 2021. The sample consists of obese, overweight men and women with diabetes mellitus, aged over 20 years, infected with SARS-CoV-2. Data were obtained through the electronic medical record of the SUS Hospital and Outpatient Management System (GSUS). Multiplex PCR method was used to determine GSTM1 and GSTT1 genetic polymorphisms. 174 individuals participated in the study, 62.6% (n = 109) female. The mean age of the participants was 56.0 years, with a mean length of stay in the intensive care unit of 13.0 days. It was possible to observe a higher frequency of need for tracheostomy among patients with GSTT1+ individually (p<0.114). In combinations, the GSTM1- /GSTT1+ genes showed a higher frequency of need for non-invasive mechanical ventilation and tracheostomy p<0.099 and p<0.076 respectively. Statistical analysis revealed the prevalence of the GSTM1+ gene among patients with diabetes mellitus (p<0.076) and cardiovascular disease (p<0.068). When compared in groups, the GSTM1+ /GSTT1+ (p<.0151) they also showed a higher prevalence of diabetes mellitus. Obese, diabetic patients infected with SARS-CoV-2 are prone to developing greater complications, even more so when they have deletion genes. This study suggests that patients with the presence of the genes evolved with greater complications and were evidenced mostly in the diabetic population and with cardiovascular diseases.